Analisis Tingkat Kepuasan Konsumen Terhadap Pelayanan PT Perintis Perlindungan Instalasi Listrik Nasional (PPILN) Area Berau - Meiriana, Yuyun (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract:This study has objective to determine the level of customer satisfaction to the public ppiln pt berau area in terms of service quality dimensions consisting reliability, responsiveness assurance emphaty, and tangible. Took samples from 100 were taken proportionally sampling method purposive random sampling. While a test hypotheses using the chi square, the t-test and analysis using importance-performance analysis.Keywords: Consumen Satisfaction, Service